An acute phase reaction with intravenous bisphosphonate use in a patient with recently diagnosed Graves' disease. Issue 8 (19th June 2017) - Gupta, Katharine; Estrella, Jane; Rajagopal, Rohit; Shanmugalingam, Praseetha; Simmons, David
Key Clinical Message: Given the immune background, we hypothesize that active Grave's hyperthyroidism is a risk factor for an acute phase reaction associated with the use of bisphosphonates. We recommend that in patients with Graves' thyrotoxicosis and hypercalcemia, consider the risk of an acute phase reaction if planning to give bisphosphonate therapy. Abstract : Given the immune background, we hypothesize that active Grave's hyperthyroidism is a risk factor for an acute phase reaction associated with the use of bisphosphonates. We recommend that in patients with Graves' thyrotoxicosis and hypercalcemia, consider the risk of an acute phase reaction if planning to give bisphosphonate therapy.